Studi Kasus: Asuhan Kebidanan pada Ibu Hamil Trimester 3 dengan Masalah Edema Kaki - Fetty Rosyadia Wachdin; Hayun Manudyaning Susilo; Ririn Ratnasari; Nida Nurhidayah (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Feet edema in pregnant women is a danger sign for pregnant women that needs to be watched out for. Leg edema can be accompanied by complications during pregnancy. According to WHO, in 2020 75% of pregnant women in the world suffered from edema in the upper extremities which generally occurred in the 2nd and 3rd trimesters. Meanwhile, 80% of pregnant women in Indonesia experienced problems with edema in the legs. (Aulia, 2020) (Sari, 2023) This study aims to address the problem of leg edema in pregnant women in the third trimester and increase mothers' knowledge about danger signs of pregnant women, especially leg edema in the final trimester. The type of research conducted is descriptive research with a case study method. Data collection methods are observational and interviews. The results of continuous midwifery care provided to Mrs. S G2P10001, 31 years old, showed problems found in antenatal care in the third trimester of pregnancy, namely the mother experienced swelling in the legs for 2 days, normal blood pressure, and a negative urine protein test. The mother was given health education about danger signs of pregnancy in the third trimester, especially eclampsia which can be characterized by edema in the legs. The mother said she understood the midwife's explanation and would be more alert.